Hunting Squarks in Higgsino LSP scenarios at the LHC - Arganda Carreras, Ernesto (2023)
Current searches for squarks are inefficient in cases when the squark does not directly decay to the lightest supersymmetric particle (LSP), because those decays are Yukawa suppressed. This occurs when producing the first two generations of squarks and when, at the same time, there are several electroweakinos lighter than those squarks. In this paper, we analyze the signal of the pair production of squarks that subsequently decay to an intermediate neutralino (?χ03) plus jets. The neutralino will then decay to the LSP (mainly Higgsino) and a Higgs. We have simulated the events and designed a discovery strategy based on a signal of two jets, four b quarks, and missing transverse energy. We obtain very promising values for the Large Hadron Collider sensitivity at 14 TeV and 300  fb−1.